The Existential‐Phenomenological Situation of Ideological Extremism. Issue 4 (23rd November 2021) - Zhao, Steven
Abstract : In this essay Steven Zhao provides an existential‐phenomenological account of radicalization and extremism. This elaboration is in response to what Zhao perceives to be the two problematically dominant perspectives of discourse on radicalization: the ideational perspective and the psychological perspective. The ideational perspective is risky because it offers an incomplete understanding of radicalization by presuming that it is the expression of cognitive errors. The psychological perspective, on the other hand, excessively individualizes radicalization as an exceptional psychological aberration that can riskily result in instructivistic preventative approaches in education. Zhao proposes the existential‐phenomenological elaboration as a supplemental articulation of radicalization that has potential to address the issues associated with these two dominant perspectives. According to this elaboration, ideological extremism is a relational phenomenon that constitutes a "dysfunctional" structure of intersubjectivity. Applying interrelated notion of subjectivity and intersubjectivity illuminates radicalization in a way that both widens the scope of ideational attributions/corrections and transcends the individualistic confines of psychopathology/psychological resilience. Ultimately, this elaboration seeks to enrich educational approaches to addressing radicalization such that preventative strategies are informed by the relational foundations intrinsic to both cognitive and psychological motivations of extremist behaviors and beliefs.